2023
DOI: 10.1186/s12889-023-15631-w
|View full text |Cite
|
Sign up to set email alerts
|

Different associations of occupational and leisure-time physical activity with the prevalence of hypertension among middle-aged community dwellers in rural Khánh Hòa, Vietnam

Abstract: Background In contrast to high-income countries where physical activity (PA), particularly leisure-time PA, has been shown to be protective against hypertension, few studies have been conducted in low- and middle-income countries. We examined the cross-sectional association between PA and hypertension prevalence among rural residents in Vietnam. Methods We used data collected in the baseline survey of a prospective cohort study, among 3000 people a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Some studies have shown an association between higher OPA and increased hypertension risk [ 14 , 15 ], including a tendency for heavy occupational lifting to increase the incidence of hypertension [ 23 ]. However, these results are not universally observed [ 12 , 16 , 17 ]. A meta-analysis has indicated no significant association between OPA and hypertension [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown an association between higher OPA and increased hypertension risk [ 14 , 15 ], including a tendency for heavy occupational lifting to increase the incidence of hypertension [ 23 ]. However, these results are not universally observed [ 12 , 16 , 17 ]. A meta-analysis has indicated no significant association between OPA and hypertension [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has indicated no significant association between OPA and hypertension [ 12 ]. Additionally, lower levels of OPA have been associated with a higher risk of hypertension [ 18 , 19 ], while higher levels of OPA have been associated with a lower risk of hypertension [ 15 , 17 ]. These discrepancies may be influenced by factors such as study populations, definitions of OPA, outcome variables, and potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, more and more studies have started to explore the association between occupational physical activity (OPA) and blood pressure (BP) in workers, but the results are controversial. Some studies have demonstrated that higher physical activity was associated with a lower risk of hypertension compared to low physical activity ( 4 , 5 ). However, a Chinese cohort study ( n = 9,350) found that high OPA workers had a 1.46 times higher risk of new-onset hypertension compared with low OPA workers ( P < 0.05) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%